2021
DOI: 10.1016/j.cattod.2020.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Processes of catalytic oxidation for the production of chemicals from softwood biomass

Abstract: Two alternative routes of softwood catalytic oxidative fractionation on cellulose products and fine chemicals are assessed.We suggested to use the process of larch wood peroxide oxidation in the medium acetic acid -water at temperatures 70-100 °C in the presence of soluble catalyst (NH 4 ) 6 Mo 7 O 24 to produce microcrystalline cellulose (35.0 wt% on wood), microfibrillated cellulose (7.5 wt% on wood), nanocrystalline cellulose (3.7 wt% on wood) and low molecular weight organic compounds (20 wt% on wood). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…The polysaccharides were extracted from the spent liquors of the catalytic and noncatalytic larch wood delignification after the cellulose isolation. The conditions for delignification were chosen on the basis of earlier study [19], where it was shown that, at a temperature of 100 °C, a hydrogen peroxide content of 6 wt%, an acetic acid of 30 wt%, and a LWR of 15, the deepest delignification of wood occurs, which ensures a residual lignin content below 1% in the cellulose product. In this case, water-soluble low-molecularweight lignin degradation products, as well as polysaccharides, pass into the solution.…”
Section: Delignification and Yield Of Polysaccharidesmentioning
confidence: 99%
See 3 more Smart Citations
“…The polysaccharides were extracted from the spent liquors of the catalytic and noncatalytic larch wood delignification after the cellulose isolation. The conditions for delignification were chosen on the basis of earlier study [19], where it was shown that, at a temperature of 100 °C, a hydrogen peroxide content of 6 wt%, an acetic acid of 30 wt%, and a LWR of 15, the deepest delignification of wood occurs, which ensures a residual lignin content below 1% in the cellulose product. In this case, water-soluble low-molecularweight lignin degradation products, as well as polysaccharides, pass into the solution.…”
Section: Delignification and Yield Of Polysaccharidesmentioning
confidence: 99%
“…As shown in Table 1, the polysaccharide yield at a process temperature of 90 °C is lower than that at 100 °C. This is due to the fact that at 100 °C the process of wood delignification is more complete [19,20] and, therefore, a greater amount of structural polysaccharides passes into liquor 1. The use of the (NH 4 ) 6 Mo 7 O 24 and MnSO 4 catalysts ensures a fairly high yield of polysaccharides already at 90 °C.…”
Section: Delignification and Yield Of Polysaccharidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Численную оптимизацию процесса каталитической пероксидной делигнификации древесины ели проводили с применением пакета прикладных программ Statgraphics Centurion XVI, блок DOE (Design of Experiment) [17].…”
Section: экспериментальная частьunclassified